ON CAPACITY TRADEOFFS IN SECURE DS-CDMA PACKET COMMUNICATIONS WITH QOS CONSTRAINTS - Sattar, F.; Mufti, M. (The Nucleus, 2012)
This paper presents a mathematical framework for analysis of effect of counter mode (CTR) encryption on the traffic capacity of packet communication systems based on direct-sequence, code-division, multiple-access (DS-CDMA). We specify QoS constraints in terms of minimum acceptable mean opinion score (MOS) of voice payload, maximum permissible resource utilization for CTR-mode re-keying and DS-CDMA processing gain. We quantify the trade-offs in system capacity as a function of these constraints. Results show that application of CTR encryption causes error expansion and respecting the QoS constraints while satisfying the desired encryption parameters results in reduction of traffic capacity